The Influence of Financial Literacy and Practical Budgeting on Financial Stability on Ecommerce Business Performance - Putri, Ririn Yuliani; Indriany, Lenny (Margin: Jurnal Lentera Managemen Keuangan, 2025)
This study explores the influence of financial literacy and budgeting practices on financial stability among the younger generation involved in e-commerce. In the context of the rapid growth of the e-commerce sector, especially in the digital era, a deep understanding of financial management is crucial for young business actors. Through a quantitative approach, this study collects data from business actors who have been operating for at least one year, with a focus on how financial literacy and budgeting practices can improve financial performance and business sustainability. The results show that both financial literacy and budgeting practices have a significant positive influence on financial stability. The application of financial literacy allows individuals to make wiser financial decisions, while effective budgeting practices help in resource management and expenditure control. These findings provide important insights for the development of relevant financial education policies and training programs, to prepare the younger generation to face financial challenges in the world of e-commerce. As such, the research not only contributes to the academic literature, but also offers practical recommendations for improving individuals' financial well-being and business sustainability in the digital age.